Al-'ilm (Ilmu Pengetahuan): Menghargai Ilmu Pengetahuan dan Belajar - Filzah Azkia Nasution; Citra Lianingsih; Naswa Kamila; Dwi Meutia Hasni (STIKes Ibnu Sina Ajibarang, 2026)
Knowledge holds a central position in Islam as it serves as the foundation for faith, moral development, and human civilization. The Hadiths of Prophet Muhammad ﷺ emphasize the importance of seeking knowledge, developing noble character, and implementing educational values in everyday life. This study aims to analyze the concept of al-‘ilm (knowledge) from the perspective of Hadith, examine the character values and ethical conduct that should be cultivated in the learning process, and explore the implementation of values that promote respect for knowledge and learning within the framework of Hadith Tarbawi. This research employs a qualitative library research method by analyzing relevant Hadiths, Islamic literature, and scholarly sources. The findings reveal that al-‘ilm in the Hadith tradition is not merely understood as knowledge acquisition but also as a means of drawing closer to Allah and developing virtuous character. The character values that should be fostered in education include honesty (ṣidq), trustworthiness and responsibility (amanah), as well as humility and patience. Furthermore, the implementation of respect for knowledge is reflected through enthusiasm for learning, worship education based on exemplary conduct, habituation, gradual learning approaches, and appreciation for knowledgeable individuals. The study implies that Hadith Tarbawi remains highly relevant in developing an Islamic educational system that emphasizes not only cognitive achievement but also character formation and spiritual development among learners.